Evaluation of imported raw materials based on the country of origin: SaleBridge Corporation - Ayan, Mahathir Mohammad (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.